Sonographic detection of central nervous system defects in the first trimester of pregnancy. (15th February 2016) - Engels, A. C.; Joyeux, L.; Brantner, C.; De Keersmaecker, B.; De Catte, L.; Baud, D.; Deprest, J.; Van Mieghem, T.
Abstract: The fetal central nervous system can already be examined in the first trimester of pregnancy. Acrania, alobar holoprosencephaly, cephaloceles, and spina bifida can confidently be diagnosed at that stage and should actively be looked for in every fetus undergoing first‐trimester ultrasound. For some other conditions, such as vermian anomalies and agenesis of the corpus callosum, markers have been identified, but the diagnosis can only be confirmed in the second trimester of gestation. For these conditions, data on sensitivity and more importantly specificity and false positives are lacking, and one should therefore be aware not to falsely reassure or scare expecting parents based on first‐trimester findings. This review summarizes the current knowledge of first‐trimester neurosonography in the normal and abnormal fetus and gives an overview of which diseases can be diagnosed. © 2016 John Wiley & Sons, Ltd.